Thrombocyte Alterations in Pregnant Women with Gestational Diabetes Mellitus - Senturk, Senol; Kagitci, Mehmet; Guvendag Guven, Emine Seda (Gynecology Obstetrics & Reproductive Medicine, 2018)
Objective: Inflammation and its complications might develop in patients diagnosed with diabetes mellitus. It is shown that number, shape and functions of thrombocytes are important for development and prediction of inflammatory process. We aimed to show the changes of number, morphology and functions of platelets in the patients with gestational diabetes mellitus. study design: In a retrospective study, 928 cases in 24-28th weeks of gestation followed regularly in the same clinic were included. We performed 75g oral glucose tolerance test to all cases. Mean platelet volume, platelet distribution width and plateletcrit values of the cases with and without gestational diabetes mellitus according to American Diabetes Association criteria were compared to evaluate the platelet count, morphology, functions and activity. Results: Platelet count and plateletcrit values of cases were significantly higher in the patients with gestational diabetes mellitus. No significant differences were found between the cases with and without gestational diabetes mellitus in mean platelet volume and platelet distribution width values. Conclusion: There is tendency to inflammation in GDM and platelets are part of inflamatuary process in human metabolism. Our findings show that, platelets are affected in GDM. We believe that further studies in this subject will help understanding of pathophysiology of GDM.